Factors Influencing Investment Decisions - Oktryani, Selvita; Trian Sandi Putra, Bayu; Agung Lestari, Muhammad (International Forum of Researchers and Lecturers, 2025)
A single paragraph, maximum 250 words. Abstract content must contain (1) an overview of the object This study aims to identify and analyze various behavioral finance factors that influence investment decisions, especially among the younger generation and individuals who invest. The method used is the Systematic Literature Review (SLR) with data sources from Google Scholar in the period 2020 to 2024. The focus of this study is on factors such as regret aversion, mental accounting, illusion of control, and overconfidence. The results of research from various journals show that these psychological factors have a significant, although varying, influence on investment decisions. Some studies confirm the strong influence of these factors, while others provide different results. Therefore, it is very important for investors and policy makers to understand these dynamics in order to improve the quality of investment decision making.